(untitled) (ModaPalavra e-periódico, 2026)
This article aims to address generalized types of sewing techniques—industrial, artisanal, and domestic—to discuss the possibility of multisewings in a world dominated by industrial monosewing. Based on a dialogue between the theories of Heidegger (2006 [1953]) and Hui (2020) on technique in the modern world, and research investigating seamstresses in Brazil, this work puts the technical role of this craft into perspective. This exercise leads to reflection on the possibility of “home-based seamstresses” practicing multiple sewing techniques simultaneously, considering their practices heterogeneous, developed throughout their trajectories, mainly because it is not an institutionalized profession. We consider the practices of “home-based seamstresses” an important object of study in relation to technique in fashion and clothing. The study suggests that a non-linear time perspective on sewing techniques, as presented in most bibliographical references in the fashion field, such as haute couture > prêt-à-porter > fast-fashion, is capable of rescuing other sewing practices.